Influência de diferentes fontes fotoativadoras na resistência adesiva de restauração indireta de resina composta - Camilotti, Veridiana (2005)
The following study aims to evaluate the influence between the different light sources in curing light of resin cement. The occlusal surfaces of twenty recently extractew undamaged third human molars were removed in order to expose dentine surface. Immediately after, the bond system (Adper Single Bond/3M ESPE ) and resin cement (RelyX ARC/ 3 M ESPE) was applied in accordance with manufacturer instructions. Second generation laboratory resin of 4 mm thickness was applied over tooth and light curing proceeded. According to light sources employed the teeth were divided in four groups: G1 – Control Optilux 401/ Demetron (QTH); G2 – L.E.Demetron/Demetron (LEDs ); G3 – Ultra-Lume LED5 (LEDs) e G4 – Optilight CL/ Gnatus (LEDs). Restored teeth were stored in physiologic serum for 24 h. After stored, teeth were sectioned into vestibule-tongue and mesial-distal to delimit an area with approximately 1 mm², the third cut was made on the base of the tooth in order to release the samples. The microtensile test was employed to reveal the bond strength values in MPa. The data underwent statistical analysis with p<0,05. No statistical significancent difference was found betweem the groups. In conclusion the resin cement bon strength of dual fotoative with LEDs showed similar adhesive resistance test those revelead when halogen lamp was used, and that there also were not differences among the different apparels LEDs used in that study.